Reserve requirements, bank runs, and optimal policies in small open economies - Eduardo J.J. Ganapolsky (Federal Reserve Bank of Atlanta, 2003)
This paper rationalizes as the outcome of an optimal policy decision the pattern of reserve requirements and other macroeconomic variables in the aftermath of a bank run. The paper develops a general equilibrium model that departs from the standard small open economy (SOE) model in three dimensions: (i) capital mobility is not perfect, (ii) there exists a costly banking system, and (iii) there is an externality affecting individual banks' decisions. The results suggest that the path of reserve requirements would depend on the type of shock that the economy receives and the effect that this shock produces on the interest rate. Interestingly, the size of the risk premium will affect the reaction of the economy to the shock. It is also shown that the dynamic adjustment will be slightly different for permanent and temporary shocks, and it will also depend on the access that the economy has to foreign funds.
Keywords: 330